Analisis Tindak Tutur Yang Mengandung Implikatur Dalam Drama Ansangu Shinderera Byouin Yakuzaishi No Shohousen - Saepul Abdul Ajis; Sudjianto Sudjianto; Helen Susanti (Universitas Pakuan, 2021)
ABSTRACT: This research discusses about the types of speech acts that contain implicatures in the drama tittled Ansangu Shinderera Byouin Yakuzaishi No Shohousen. The main focus of this thesis is to identify dialogues in the drama that fall into the five speech acts qualifications according to Searle which have implicit intentions. The theory used in this thesis is a pragmatic theory which examines what a person means in his speech when communicating. This research used a descriptive qualitative method. In conclusion, in the Ansangu Shinderera Byouin Yakuzaishi No Shohousen drama found the five types of illocutionary speech acts that classified by Searle and containing implicatures with the intention of prohibiting, refusing, expressing ability, desire, request, plead, insinuating, and command.